The expression status of human epidermal growth factor receptor 2 in epithelial ovarian cancer in Ibadan, Nigeria (2015)
Breast cancer is the most common cancer among females in Nigeria. Bilateral breast cancer can occur synchronously or metachronously. We report three different cases of bilateral breast cancer in three female patients managed by the Ibadan Multidisciplinary Breast Tumour Board, domiciled at the University College Hospital (UCH), over a 3-year period. Two of these patients had synchronous bilateral breast cancer and developed cancer in the second breast during the course of management. These case reports may therefore stimulate further research on the clinicopathological features and the progression of bilateral breast cancer among females, especially in our environment. Our patients were premenopausal and the immunochemistry of the tumours showed a triple-negative immunophenotype. The other features of presentation, investigation, diagnosis and follow-up care are the highlights of this presentation.